ZNACZENIE ALMANACHU 1C Z KODEKSU DREZDEŃSKIEGO DLA ROZWOJU EPIGRAFIKI MAJAŃSKIEJ - Jagodziński , Kajetan (Studia Europaea Gnesnensia, 2017)
This papers seeks to demonstrate the tremendous importance of the usually omitted first page of the Dresden Codex for the ongoing process of deciphering Mayan script. As an example, one could quote the recently identified Mayan term denoting a loincloth (Span. braguero, taparrabo) in the almanac 1c, which may be found on the page in question. Furthermore, the author critically discusses all possible forms in which the word can have been written, as it still defies being deciphered completely.